The fox spirit, the stone maiden, and other transgender histories from late imperial China - Sommer, Matthew Harvey, 1961- (Columbia University Press, 2024)
"In Transgender in Imperial China, Matthew Sommer offers a close reading of a series of remarkable, well-documented court cases from the 18th and 19th century Qing dynasty legal archives that deal with sex and gender difference. The book explores practices in their specific historical context and avoids imposing trans-historical identities on people in the past, understanding, in the vein of Susan Stryker's work, that "transgender people" are those who "move away from" the gender assigned at birth and "cross over" the gender boundaries imposed by their society, without assuming any specific motivation or destination for that movement. Sommer details the experience of individuals assigned male at birth who were living as women (and were punished very harshly for the crime of "masquerading in women's attire"), but also includes under the sign "transgender" a range of personae not usually considered in this context, such as cross-dressing "boy actresses" of the opera and those who "left the family" by becoming Buddhist or Daoist clergy or eunuchs in imperial service and renouncing normative gender roles based on marriage and procreation. These cases explore a range of themes in Chinese law, society, and culture, and illuminate how many forms of gender transgression were sanctioned by law in Qing society. In considering all of these scenarios together, Sommer's book unpacks the full story of how sex and gender were understood in the Qing era"--